A Case Report: Post-Traumatic Stress Disorder (PTSD) with Thyrotoxicosis and Psychosocial Stress - Masyita Kusuma Maharani; Hafid Algristian; Ariyani Sri Suwarti (Sinergi International Journal of Psychology, 2026)
Post-Traumatic Stress Disorder (PTSD) is a psychiatric condition triggered by trauma, often exacerbated by medical comorbidities like thyrotoxicosis. This report aims to illustrate the complex interaction between PTSD, endocrine dysfunction, and psychosocial stress, highlighting the need for an integrated treatment approach. This case report is based on a clinical case of a 31-year-old female with PTSD and comorbid thyrotoxicosis treated at a hospital in Indonesia. Data were collected through clinical history, physical and psychiatric examinations, and a review of relevant literature. The patient developed PTSD symptoms following a motorcycle accident, including nightmares, hyperarousal, insomnia, and avoidance behavior. Her pre-existing thyrotoxicosis amplified anxiety and physiological arousal, while psychosocial stressors such as legal issues and unemployment perpetuated her symptoms. A combined treatment of Sertraline 50 mg/day, short-term Alprazolam, trauma-focused therapy, and spiritual coping strategies resulted in initial improvement in anxiety and emotional regulation. Managing PTSD with comorbid thyrotoxicosis and psychosocial stress requires a biopsychosocial-endocrine approach. Coordinated pharmacological, psychotherapeutic, and psychosocial interventions are essential for symptom control and functional recovery. This case underscores the importance of multidisciplinary collaboration in complex PTSD presentations.